Signal-flow graphs: Direct method of reduction and MATLAB implementation - Teixeira, MCM; Marchesi, H. F.; Assuncao, E. (Institute of Electrical and Electronics Engineers (IEEE), 2001)
Block diagrams and signal-flow graphs are used to represent and to obtain the transfer function of interconnected systems. The reduction of signal-flow graphs is considered simpler than the reduction of block diagrams for systems with complex interrelationships. Signal-flow graphs reduction can be made without graphic manipulations of diagrams, and it is attractive for a computational implementation. In this paper the authors propose a computational method for direct reduction of signal-flow graphs. This method uses results presented in this paper about the calculation of literal determinants without symbolic mathematics tools. The Cramer's rule is applied for the solution of a set of linear equations, A program in MATLAB language for reduction of signal-flow graphs with the proposed method is presented.
Keywords: Mason's rule; signal-flow graphs; symbolic calculations; transfer functions